Use ofBang marking in the management of the cost of food and beverages in the hotel: sector (Case study in a sample of hotels in Baghdad governorate) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The competition in the hotel sector, globalization and the development of new information have forced the sector to continuously seek new techniques and arrangements to remain competitive through hotel industry companies, including Benchmarking and the application of this method in the hotel sector. The selection of the Rashid International Hotel by the Ministry of Tourism as a leading hotel or benchmark for comparison of other hotels in Iraq, and the selection of two hotels in Baghdad for comparison, namely (Ishtar International Hotel, Baghdad International Hotel) and the choice also by the Ministry of Tourism, N is to correct the course of practice to manage the cost and diagnosis of the weakness of the strengths and weaknesses in the management of the cost of food and drinks for these hotels, and development in accordance with the nature of the organizations and the nature of the accounting system used, and through the research was concluded to the weakness in cost management at the Baghdad International Hotel, As well as highlighting the strengths and weaknesses of the Ishtar Sherton Hotel. Through this comparison, hotels have been able to discover their strengths and weaknesses in managing the cost of food and beverages from leading hotels in this area, and analysis and diagnosis and conducts the best practices in its operations.With an effective role of benchmarking in the evaluation and development of hotel performance through the development of standards for cost management through comparison